Mental health stigma and mental health knoewledge in Porto Metropolitan Area population: cross-sectional study - Cunha, Ana Rafaela Azevedo (2022)
The community’s stigma associated with mental illness has been linked to low mental health literacy, lack of information or understanding of mental illness, and its inherent symptoms. In Portugal, this population targets prejudice and discrimination in the diferente contexts where it is inserted. Toassess the sitgma and discrimination against people with lived experience of mental illness residing in the Metropolitan Area of Porto, Portugal. In this analytical observational study, we surveyed 3980 individuals living in the metropolitan área of Porto and aged between 18 and 96 years, using the Portuguese version of the Mental health knowledge Schedule (MAKS). The questionnaire dimensions with the highest mean scores were employment and psychotherapy, followed by support and pharmacological treatment. Seeking help and recovery were the dimensions with the lowest mean scores. Depression, schizophrenia, and bipolar disorder were the conditions most recognized as mental disorders. Grief was the condition least recognized by the participants. These results suggest that the participants presente correct representations and perceptions about mental illnesses, indicating that negative beliefs and stereotypes are not significantly rooted in this sample. The study sample representative of the Portuguese population of the metropolitan are of Porto reveals moderate levels of mental health literacy. However, the scores of seeking help and recovery may reflect the need for publica nt-stigma campaigns that discuss these factos, given the progressive reduction of social stigma.